MODELING COMMERCE IN TERMS OF CHEMICAL REACTIONS - DICKENS, Robert (Theoretical and Practical Research in Economic Fields, 2022)
After first explaining the basis for such modeling, namely, changes in money in commerce appearing to mirror changes in free energy in coupled chemical reactions, with a striking correspondence between profit and reduction in free energy, a model of two ‘coupled Deliveries’ is constructed, noting the need also to model supply and demand, and using the somewhat literal example of a taxi journey up a hill, to help make sense of the approach. The modeling of supply and demand is then explained, the effect on prices being attributed to the spreading-out of energy from sellers to buyers. An expression for this effect is then derived, in terms of the corresponding concentrating of money. Various implications of the model are then expounded, concerning the nature of money, price and its relationship to value, and intelligence, and some supporting evidence given. Two secondary implications, concerning economics and political science, are then discussed to conclude.